2020
DOI: 10.1186/s12998-020-00353-2
|View full text |Cite
|
Sign up to set email alerts
|

Misinformation, chiropractic, and the COVID-19 pandemic

Abstract: Background In March 2020, the World Health Organization elevated the coronavirus disease (COVID-19) epidemic to a pandemic and called for urgent and aggressive action worldwide. Public health experts have communicated clear and emphatic strategies to prevent the spread of COVID-19. Hygiene rules and social distancing practices have been implemented by entire populations, including ‘stay-at-home’ orders in many countries. The long-term health and economic consequences of the COVID-19 pandemic are not yet known.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that massage therapy or aromatherapy massage can alleviate stress-induced psychophysiological discomfort, lower blood pressure and heart rates, decrease stress hormone levels, reduce fatigue, and improve sleep quality [ 6 , 31 ]. A recently published article has indicated that chiropractic care or spinal manipulation can provide management for musculoskeletal disorders; however, the inappropriate information from social media and the internet provided by chiropractic regulatory agencies which claimed that it can enhance immunity to protect against COVID-19 should be strictly noted by healthcare providers [ 40 ]. One cross-sectional survey also indicated that massage, TCM, and chiropractic treatments can cause adverse side-effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that massage therapy or aromatherapy massage can alleviate stress-induced psychophysiological discomfort, lower blood pressure and heart rates, decrease stress hormone levels, reduce fatigue, and improve sleep quality [ 6 , 31 ]. A recently published article has indicated that chiropractic care or spinal manipulation can provide management for musculoskeletal disorders; however, the inappropriate information from social media and the internet provided by chiropractic regulatory agencies which claimed that it can enhance immunity to protect against COVID-19 should be strictly noted by healthcare providers [ 40 ]. One cross-sectional survey also indicated that massage, TCM, and chiropractic treatments can cause adverse side-effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most chiropractors in our study identified recognised government agencies and professional bodies as their most trusted sources when seeking COVID-19 public health information. However, a smaller number of chiropractors have made claims on social media that chiropractic spinal manipulation reduces the adverse impact of COVID-19 [ 11 , 12 , 14 ], claims that appear to conflict with current clinical research evidence [ 51 , 52 ]. In response, leaders of the chiropractic research community [ 53 ], chiropractic regulatory bodies [ 15 , 16 ] and chiropractic professional associations [ 54 – 57 ] have made efforts to redress such claims within the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Infection control standards for chiropractors vary according to country and specific jurisdictional mandates should be the best predictor of professional behaviour. However, limited information suggests chiropractors practising under a subluxation-based paradigm may hold different public health views to that of government health authorities and/or scientific consensus regarding COVID-19, including a belief that chiropractic adjustments (spinal manipulation) can boost the immune response to COVID-19 infection, improving protection against the disease [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Included in these “immune-boosting” interventions is Spinal Manipulative Therapy (SMT) [ 8 ]. Most commonly delivered by chiropractors in the management of musculoskeletal conditions, SMT is sometimes promoted as having systemic effects including the ability to boost immunity [ 9 ]. While there is evidence supporting the use of SMT as an intervention for low back pain and other MSK conditions [ 10 ], we are not aware of any robust evidence that SMT, nor a specific profession that provides SMT, creates a clinically meaningful improvement in the human immune system [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%